Comparative analysis of diversity and environmental niches of soil bacterial, archaeal, fungal and protist communities reveal niche divergences along environmental gradients in the Alps. (June 2022) - Malard, Lucie A.; Mod, Heidi K.; Guex, Nicolas; Broennimann, Olivier; Yashiro, Erika; Lara, Enrique; Mitchell, Edward A.D.; Niculita-Hirzel, Helene; Guisan, Antoine
Abstract: Although widely used in ecology, comparative analyses of diversity and niche properties are still lacking for microorganisms, especially focusing on niche variations. Quantifying the niches of microbial taxa is necessary to then forecast how taxa and the communities they compose might respond to environmental changes. In this study, we first identified important topoclimatic, edaphic, spatial and biotic drivers of the alpha and beta diversity of bacterial, archaeal, fungal and protist communities. Then, we calculated the niche breadth and position of each taxon along the important environmental gradients to determine how these vary within and among the taxonomic groups. We found that edaphic properties were the most important drivers of both, community diversity and composition, for all microbial groups. Protists and bacteria presented the largest niche breadths on average, followed by archaea, with fungi displaying the smallest. Niche breadth generally decreased towards environmental extremes, especially along edaphic gradients, suggesting increased specialization of microbial taxa in highly selective environments. Overall, we showed that microorganisms have well defined niches, as do macro-organisms, likely driving part of the observed spatial patterns of community variations. Assessing niche variation more widely in microbial ecology should open new perspectives, especially to tackle global change effects on microbes. Highlights: We studied bacterial, archaeal, fungal and protist communities in Alpine soils. Edaphic properties, particularly pH, drive alpha and beta diversity of all groups. Protists and Bacteria have, on average, larger environmental niche breadths. On average, fungi proportionally harbor more generalist taxa while bacteria harbor more specialist taxa than any other group. Small niche breadth towards environmental extremes suggests increased specialization.